PENGARUH DAYA TARIK, FASILITAS DAN AKSESIBILITAS TERHADAP KEPUTUSAN WISATAWAN ASING BERKUNJUNG KEMBALI KE ALOITA RESORT DI KAB. KEP. MENTAWAI (Jurnal Pelangi : Research of Education and Development, 2014)
attractiveness and accessibility of the facility to the visit of foreign tourists to Aloita Resort in the Mentawai Island regency. The population was all foreign tourists on the time of the research conducted. Samples were 50 respondents; sampling technique was accidental sampling method. The kinds of data used were primary and secondary data. Data were collected by using a questionnaire. The technique used to perform the analysis was an analytical technique known as path analysis. For data processing, the researcher,  uses computer with SPSS version 17:00. The results shows that the attractiveness (X1) significantly affects the decision of foreign tourists to visit. Facilities (X2) significantly affects the foreign tourists to visit and accessibility (X3) significantly affects the decision of foreign tourists to visit.